The USC Trojans football encyclopedia - Shmelter, Richard J., 1959- (McFarland & Company, Inc., Publishers, 2014)
"This reference chronicles the history of USC football from its first-ever game on November 14, 1888 through 2012. Synopses of each season include game-by-game summaries, final records, poll rankings, and team leaders in statistical categories. Biographies of head coaches, roster of players, traditions, and catalog of honors received by players and coaches complete this encyclopedia"--